(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This review aims to analyze the mechanisms of cryoinjury, evaluate the functional roles of cryoprotective agents, and systematize emerging strategies to mitigate cryoprotective agents toxicity in stem cell preservation. Methods: A comprehensive literature synthesis was conducted, focusing on ice crystallization kinetics, the mechanistic pathways of permeating and non-permeating cryoprotective agents, and current optimization protocols for cryopreservation. Results: Cryopreservation induces cellular damage primarily through intracellular ice formation and osmotic shock. While traditional cryoprotective agents, particularly dimethyl sulfoxide, provide robust protection, their significant cytotoxicity remains a major challenge. Current advancements follow two parallel trajectories: (1) Optimizing traditional protocols by controlling osmotic kinetics, utilizing sugar buffers, and employing low-concentration cryoprotective agents cocktails at reduced exposure temperatures; (2) Developing next-generation biomaterials, including antifreeze proteins, synthetic ice blockers, and biocompatible solutes. Conclusion: Optimizing cryoprotective agents is critical for maintaining the structural integrity and functional viability of stem cells. Future trends are shifting from high-toxicity single agents toward multi-component synergistic mixtures and biomimetic materials, ensuring maximal safety and efficacy for clinical cell-based therapies.